The analysis of the bankruptcy of enterprises exemplified by the Visegrad Group - Krajewski, Jarosław; Tokarski, Andrzej; Tokarski, Maciej (Journal of Business Economics and Management, 2020)
The phenomenon of enterprises bankruptcy is an extremely complex process of economic, legal, social and even psychological nature. In the developed countries, the first studies on forecasting bankruptcy date to the early 20th century. In Central and Eastern Europe, due to, among other factors, the geopolitical situation and the introduced economic system, this issue became the subject of researchers’ interest only in the 1990s. The universality and complexity of the phenomenon incline the Authors to make an attempt to identify the scale of the bankruptcy processes in the states of the Visegrad Group (V4). The countries of V4 were selected because of their common history and similar economic development. The aim of this article is to analyze the dynamics of the phenomenon of bankruptcy of enterprises in the states of the V4 Group in the years 2005–2016 on the basis of the data taken from the Credit reform reports. The estimation of trend models in time series on the basis of the bankruptcy in the Visegrad Group countries in the years 2005–2016 was used in the article as the primary research method. The descriptive analysis was also applied in the article.